Ethnomedicin Studies and Antimicrobial Activity Tests of Plants Used in The Tengger Tribal Community - Yaya Sulthon Aziz; Jason Merari Peranginangin; Titik Sunarni (LPPM Universitas Duta Bangsa Surakarta, 2019)
Based on the medicinal plants used by the Tengger tribe and their vulnerability to antibiotic resistance, it is necessary to develop new antimicrobial drugs that are sourced from natural ingredients. This study is to determine the use of plants as a traditional medicine in the Tengger tribe which has the potential as an antimicrobial. Determination of informants in the Tengger Tribe with snowball sampling. Antimicrobial plants that have UV and ICF values close to 1 macerated with 96% ethanol. Ethanol extract, water fraction, ethyl acetate fraction and n-hexane fraction were made at concentrations of 40, 20, 10, 5, and 2.5%. Antimicrobial test by dilution method, each concentration was tested on Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, Salmonella typhi, and Candida albicans. The results showed 31 types of disease, 47 medicinal plants and 60 traditional ingredients in the Tengger tribe. Based on UV and ICF values 9 types of antimicrobial diseases and 4 potential medicinal plants were obtained. Antimicrobial medicinal plants used are Radicula armoracia, Artemisia vulgaris, Prunus persia, and Rapanus raphanistrum. Antimicrobial activity is best shown in the fraction n-hexane in all test plants. The four medicinal plants used by the Tengger tribe have the potential to be new antimicrobials